2019
DOI: 10.31254/jmr.2019.5405
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge regarding Heart Failure: A Reflection on Current Disease Knowledge State among Iranian Patients with Heart Failure

Abstract: Background: Heart failure (HF) is a serious problem with an increasing prevalence globally. Low level of HF knowledge may cause low compliance and low quality of life and, poor self-care. On the other hand, assessing the level of HF knowledge is necessary in order to apply educational programs. Aims and objectives: the aim was to determine knowledge regarding HF among Iranian patients with HF. Study Design: This was a cross sectional study. Setting: We conducted this study at the HF clinic of Tehran Heart Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Patients who had good knowledge about heart failure were 3.4 times more likely to have adhered to the recommendations self-care behaviour compared with those who had poor knowledge about heart failure. The result of this finding is congruent with studies conducted in Egypt, 41 Iran, 49 Singapore 50 and the Netherlands. 39 Heart failure patients who have a good understanding of heart failure may perform the recommended self-care behaviour than patients who have inadequate knowledge about heart failure.…”
Section: Discussionsupporting
confidence: 89%
“…Patients who had good knowledge about heart failure were 3.4 times more likely to have adhered to the recommendations self-care behaviour compared with those who had poor knowledge about heart failure. The result of this finding is congruent with studies conducted in Egypt, 41 Iran, 49 Singapore 50 and the Netherlands. 39 Heart failure patients who have a good understanding of heart failure may perform the recommended self-care behaviour than patients who have inadequate knowledge about heart failure.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with Ng'ang’a-Oginga (2016) in Kenya who reported that 89% ( n = 288) had inadequate knowledge and suboptimal level of self-care in HF. In another study in Iran, Nomali et al (2019) noted that 50% ( n = 190) of their study population demonstrated poor knowledge of HF. Similarly, in Ethiopia, Hailu Gebru et al (2020) revealed a poor self-care behavior rate of 45.8% among Ethiopian patients.…”
Section: Discussion Of Findingsmentioning
confidence: 90%
“…Were positively correlated at p<0.01 and exercise for 30 minutes were negatively correlated at p<0.05. Mahin Nomali, Kian Alipasandi (2019) [19] conducted a cross sectional study on Knowledge regarding Heart Failure A Reflection on Current Disease Knowledge State among Iranian Patients with Heart. The aim of the study was to determine the knowledge regarding HF among Iranian patients with HF.…”
Section: Discussionmentioning
confidence: 99%